Systematic literature review on the implementation of the Six Sigma approach in education - Siti Hannah Sabtu; Mohd Effendi@Ewan Mohd Matore (Institute of Advanced Engineering and Science, 2024)
The quality of teaching and pedagogical practices of teachers is a global issue in education. The success of Six Sigma in several industries stimulates its potential to be applied in the field of education. However, discussions related to Six Sigma development in systematic education are still very limited. Therefore, this systematic literature study was conducted to synthesize empirical data on the implementation of the Six Sigma approach in education. This study focuses on two main objectives, namely, to identify the trends in the implementation of the Six Sigma approach in education based on national and year tendencies as well as to identify research sampling trends and the focus of the field of study. The Web of Science and Scopus databases have been used based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA). The findings of systematic literature articles showed that India is the most dominant country conducting Six Sigma studies in education. Furthermore, related studies were conducted the most in 2017. In addition, the research samples are also more focused on the context of higher education institutions. These findings help improve the general understanding of Six Sigma in education to improve the quality of teachers in schools further.